2014
DOI: 10.1088/1752-7155/8/4/046010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breath gases, including acetone, with blood glucose and blood ketones in children and adolescents with type 1 diabetes

Abstract: Previous studies have suggested that breath gases may be related to simultaneous blood glucose and blood ketone levels in adults with type 2 and type 1 diabetes. The aims of this study were to investigate these relationships in children and young people with type 1 diabetes in order to assess the efficacy of a simple breath test as a non-invasive means of diabetes management. Gases were collected in breath bags and measurements were compared with capillary blood glucose and ketone levels taken at the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 22 publications
6
49
0
Order By: Relevance
“…BK ranges 0-0.5 mmol/L and 0-4.3 mmol/L in the healthy and T1D subjects respectively, with corresponding global means of 0.16 and 0.25 (mmol/L). The results indicate that the T1D subjects have a higher mean BA concentration than the healthy controls, which is consistent with the published data in the literatures [3,26,[30][31][32].…”
Section: Imba Imbg and Imbk Over 30 Dayssupporting
confidence: 92%
See 2 more Smart Citations
“…BK ranges 0-0.5 mmol/L and 0-4.3 mmol/L in the healthy and T1D subjects respectively, with corresponding global means of 0.16 and 0.25 (mmol/L). The results indicate that the T1D subjects have a higher mean BA concentration than the healthy controls, which is consistent with the published data in the literatures [3,26,[30][31][32].…”
Section: Imba Imbg and Imbk Over 30 Dayssupporting
confidence: 92%
“…An elevated mean BA in T1D patients was also observed in Wang et al work, in which BA in 34 T1D patients and 15 healthy individuals was measured using a CRDS-based breath acetone analyzer [26]. In a recent work by Blaikie et al BA in 113 young T1D patients (age of 7-18) in a clinic at the Oxford Children's Hospital was measured using a softionization mass spectrometer [32]. Their results show that the average value (0.51 ppm) is higher than that found for a healthy cohort of the same age group reported by Spanel et al [9].…”
Section: Correlation Of Breath Acetone To Blood Glucosementioning
confidence: 55%
See 1 more Smart Citation
“…Among the three biomarkers, β-hydroxybutyric acid was regarded as an intermediate product of energy metabolism and the diabetes diagnosis biomarker, its metabolic level had a significant increase due to peripheral lipolysis induced by insulin resistance (Blaikie et al, 2014;Bresciani, Pietra, Corradin, Giunti, & Fracassi, 2014). Our data also showed that HF diet caused a significant increase in serum β-hydroxybutyric acid level.…”
Section: Discussionsupporting
confidence: 54%
“…VOCs were measured by soft-ionization mass spectrometry (V&F AIRSENSE Compact Ion Molecule Reaction Mass Spectrometer) by a researcher blinded to clamp glucose values (2). VOC values were adjusted to 5% exhaled CO 2 .…”
mentioning
confidence: 99%